A Rare Presentation of a Bi-Maxillary Brown Tumour due to Secondary Hyperparathyroidism - Cheboh Cho-Fon; Zilefac Brian Ngokwe; Obolo Nwaga Ines (Hindawi Limited, 2023)
Brown tumours are localized bone lesions, seen in patients with high parathyroid hormone levels. This can be due to primary hyperparathyroidism, which occurs more often in neoplasms of the parathyroid gland or due to secondary hyperparathyroidism more often seen as a result of renal impairment. Facial involvement is rare, with most reports focusing on long and axial bones. However, the mandibular bone is often the only bone affected. Here, we report a rare case of a bi-maxillary attainment of brown tumour in a patient with secondary hyperparathyroidism due to chronic kidney disease.